Vivendo à sombra do colapso: a clínica psicanalítica com pacientes traumatizados - Vieira, Marcus Rodrigues Jacobina (2020)
From the researcher's clinical experience with two traumatized patients, the interest in understanding how the trauma participated in the genesis of their psychic illness was aroused, and how the psychic organizations resulting from these traumas manifested themselves in the clinical situation, in the transfer, countertransference and treatment attempts during their analysis processes. Other questions that emerged during the research were: did what Ferenczi called fear of madness, traumatic loneliness and what Winnicott called fear of collapse manifest in the clinical situation? Could it be that in the functioning of the patients, defenses were present corresponding to what the two authors identify as pathological fission? We seek to elucidate these issues and make considerations about the types of interventions that the analyst was led to adopt in an attempt to help these two patients. This work proposes to research the psychoanalytic clinic of early traumatized patients based on the theories described by Sandor Ferenczi, Donald Winnicott and Michael Balint, both in psychopathological terms and in the ethics and technique of these authors, with regard to clinical and therapeutic procedures for the treatment of these patients